GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 18856 species occurrences available in GBIF matching the query: TaxonKey: 2704353. The dataset includes 18856 records from 177 constituent datasets: 6 records from Vascular plants of south-central China. 1 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 560 records from Missouri Botanical Garden. 1 records from Biological and palaeontological collection and observation data MNHNL. 3 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 164 records from Herbarium (ICEL). 3 records from iNaturalist research-grade observations. 53 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 219 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 26 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 2 records from Institut Botanic de Barcelona, BC. 2 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 427 records from Tromsø Museum, Vascular plants. 56 records from Harvard University Herbaria. 3 records from Flora d'Andorra. 1 records from Flora exsiccata Bavarica. 4 records from Botany Division, Yale Peabody Museum. 50 records from The AAU Herbarium Database. 76 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 777 records from Vascular Plant Herbarium, Oslo (O). 64 records from Kathryn Kalmbach Herbarium. 2 records from Herbario de la Universidad de Sevilla, SEV-Historico. 152 records from NatureServe Network Species Occurrence Data. 6 records from IAC - Herbário do Instituto Agronômico de Campinas. 17 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 498 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 275 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 8 records from R. L. McGregor Herbarium Vascular Plants Collection. 12 records from Bernice P. Bishop Museum. 96 records from New Mexico Biodiversity Collections Consortium database. 13 records from Fundación Miguel Lillo - Colección Fanerogámica. 17 records from Arizona State University Vascular Plant Herbarium. 10 records from University of Lethbridge Herbarium (LEA). 1 records from Vascular Herbarium, NMBU. 3 records from Instituto de Ciencias Naturales. 2 records from naturgucker. 1 records from Carnet en Ligne. 2 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from Louisiana State University Herbarium - Vascular Plants. 248 records from The Himalayan Uplands Plant database (HUP Version 1). 6 records from EURISCO, The European Genetic Resources Search Catalogue. 4 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 41 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 1 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 8 records from SysTax - Botanical Gardens. 320 records from Naturalis Biodiversity Center (NL) - Botany. 338 records from Canadian Museum of Nature Herbarium. 1 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 94 records from Herbarium of The New York Botanical Garden. 38 records from CONN. 811 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 74 records from Royal Botanic Garden Edinburgh Herbarium (E). 28 records from Colección de Herbario. 163 records from Instituto de Botánica Darwinion. 1 records from EKY_Darwincore. 1 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 63 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 3 records from Herbario de la Universidad de Sevilla, SEV. 10 records from Plant. 2 records from Leiner-Herbar Konstanz. 1 records from herbario. 1 records from SANT herbarium vascular plants collection. 211 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 136 records from National vegetation diversity inventory and mapping plan. 6 records from Botanical Museum, Copenhagen. Database of type specimens. 2 records from Herbarium of Jyväskylä University Museum. 10 records from Herbarium Berolinense. 225 records from University of Alberta Museums, Vascular Plant Herbarium. 10 records from inatura - Erlebnis Naturschau Dornbirn. 26 records from H.A. Stephens Herbarium. 42 records from E. C. Smith Herbarium (ACAD). 5 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 35 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 2 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 168 records from Specimen Database of Colorado Vascular Plants. 19 records from Database of Native Plants in Taiwan. 83 records from Geneva Herbarium – General Collection (G). 3 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 22 records from Natural History Museum, Vienna - Herbarium W. 212 records from Vascular Plants, Field notes, Trondheim (TRH). 31 records from OHN. 8 records from Phytochorologie des départements français. 242 records from University of Alberta Vascular Plant Herbarium (ALTA). 25 records from Herbarium of Taiwan Forestry Research Institute. 7 records from Green Plant Herbarium (TRT). 78 records from Herbarium (AMNH). 1 records from Herbarium specimens of Limoges university (LIMO). 1 records from Natural History Museum Maastricht (NL) - Herbarium. 4 records from Herbarium areqvipense (HUSA). 8 records from Jordal. 1 records from Plant specimens of Hokkaido University Museum. 6 records from Nationaal Herbarium Nederland. 2 records from WII Herbarium Dataset. 4 records from Herbarium de Geo. B. Hinton, México. 285 records from CAS Botany (BOT). 112 records from Vascular Plant Collection. 1 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 165 records from UCJEPS TAPIR Provider. 1 records from Herbarium specimens of CBNA (GAP). 131 records from Database Schema for UC Davis [Herbarium Labels]. 5 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 70 records from Botany (UPS). 21 records from California State University, Chico. 281 records from Consortium of California Herbaria. 4 records from Nordic Genetic Resources. 15 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 20 records from OAC-BIO Herbarium. 11 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 103 records from BioFokus. 1 records from PACA-AGP - Herbarium Anchieta. 12 records from Allan Herbarium (CHR). 2 records from Botanic Garden of the Finnish Museum of Natural History. 2 records from NINA botanical collection. 244 records from svalbardflora.net. 10 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 2 records from Herbario de la Universidad de Arizona, EUA. 2 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1 records from DAO Herbarium Type Specimens. 3 records from KNWR Herbarium Collection. 60 records from NSW herbarium collection. 27 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 28 records from United States National Plant Germplasm System Collection. 34 records from Geographically tagged INSDC sequences. 1 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 511 records from INPN - Données flore des CBN agrégées par la FCBN. 6 records from PRECIS. 425 records from Norwegian Species Observation Service. 1 records from New Zealand National Vegetation Survey Databank. 1 records from MISS_DC_01MAR2006. 20 records from Vascular Plants Collection of National Museum of Nature and Science. 872 records from Vascular Plants, Field notes, Oslo (O). 28 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from OUPR - Herbário "Professor José Badini". 60 records from UA Herbarium. 23 records from Biodiversitätsdatenbank des Landes Salzburg. 74 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 292 records from Vascular Plant Herbarium, Trondheim (TRH). 3 records from Flora Novo Galiciana-Gramineae. 274 records from NMNH occurrence DwC-A. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 36 records from Natural History Museum (London) Collection Specimens. 5 records from Ecofact. 71 records from Marie-Victorin Herbarium (MT). 2 records from Flora vascular del cerro El Zamorano. 5 records from ANTARCTIC PLANT DATABASE. 20 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 1 records from Specimens of G. Fenoul Herbarium (FEN). 1 records from SBT-Living. 66 records from The digitization of plant specimens of NTU. 2 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 179 records from Tiroler Landesmuseum Ferdinandeum. 3 records from Herbarium Senckenbergianum (FR). 1246 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 546 records from Phanerogamic Botanical Collections (S). 2 records from Field Museum of Natural History (Botany) Seed Plant Collection. 24 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 2 records from Plant in Baekdu Mountain (KIDR-PL). 417 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 44 records from Australian National Herbarium (CANB). 32 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 101 records from Colorado State University Herbarium. 9 records from Flora genérica de las gramíneas del estado de Tlaxcala. 149 records from USU-UTC Specimen Database. 44 records from Repatriación de datos del Herbario de Arizona (ARIZ). 279 records from Artdata. 20 records from Lund Botanical Museum (LD). 280 records from Australia's Virtual Herbarium. 933 records from Consortium of California Herbaria. 65 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Polish gene bank – passport data of plants accessions which are important in human life. 2230 records from Observational database of Icelandic plants. 123 records from Vascular Plant Herbarium, UiB. 13 records from Species plots from the Norwegian Vegetation Mapping Programme. 4 records from Herbarium (Åbo Akademi), Centre for Biodiversity, University of Turku (TURA). 11 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 1 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 133 records from OEH Atlas of NSW Wildlife.
Keywords: GBIF; biodiversity; species occurrences